Inhibition of HIV-1 by curcumin A, a novel curcumin analog - Kumari N; Kulkarni AA; Lin X; McLean C; Ammosova T; Ivanov A; Hipolito M; Nekhai S; Nwulia E (Dove Medical Press, 2015)
Namita Kumari,1,2,* Amol A Kulkarni,3,* Xionghao Lin,2 Charlee McLean,1 Tatiana Ammosova,2 Andrey Ivanov,2 Maria Hipolito,1 Sergei Nekhai,2 Evaristus Nwulia11Translational Neuroscience Laboratory, 2Department of Medicine, Center for Sickle Cell Disease, College of Medicine, 3College of Pharmacy, Howard University, Washington, DC, USA*These authors contributed equally to this study Abstract: Despite the remarkable success of combination antiretroviral therapy at curtailing HIV progression, emergence of drug-resistant viruses, chronic low-grade inflammation, and adverse effects of combination antiretroviral therapy treatments, including metabolic disorders collectively present the impetus for development of newer and safer antiretroviral drugs. Curcumin, a phytochemical compound, was previously reported to have some in vitro anti-HIV and anti-inflammatory activities, but poor bioavailability has limited its clinical utility. To circumvent the bioavailability problem, we derivatized curcumin to sustain retro-aldol decomposition at physiological pH. The lead compound derived, curcumin A, showed increased stability, especially in murine serum where it was stable for up to 25 hours, as compared to curcumin that only had a half-life of 10 hours. Both curcumin and curcumin A showed similar inhibition of one round of HIV-1 infection in cultured lymphoblastoid (also called CEM) T cells (IC50=0.7 µM). But in primary peripheral blood mononuclear cells, curcumin A inhibited HIV-1 more potently (IC50=2 µM) compared to curcumin (IC50=12 µM). Analysis of specific steps of HIV-1 replication showed that curcumin A inhibited HIV-1 reverse transcription, but had no effect on HIV-1 long terminal repeat basal or Tat-induced transcription, or NF-κB-driven transcription at low concentrations that affected reverse transcription. Finally, we showed curcumin A induced expression of HO-1 and decreased cell cycle progression of T cells. Our findings thus indicate that altering the core structure of curcumin could yield more stable compounds with potent antiretroviral and anti-inflammatory activities. Keywords: curcumin A, HIV-1, reverse transcription, heme oxygenase-1